Siemens key account management : lost in Central Asia? - Yue, Tao, active 2024 (London : Rotterdam School of Management, Erasmus University, 2024)
Since the mid-1990s, Siemens AG has adapted its business processes and internal structure to the expected future competitive environment in order to make the company faster, more focused, and more efficient. In this effort, customer-centric KAM programs (Siemens One) have evolved. Siemens One is a proven success that helped the company get through the financial crisis by cutting costs, focusing on core business, and strengthening customer relationship. While Siemens One continues to mature day by day, Siemens still encounters challenges in managing key accounts at the national or regional level. The case uses Siemens KAM program for EuroBric in Tamerstan as an example to illustrate two main issues that currently face the company: 1. How to align practices of two equally complex multinational organizations and 2. How to strike a balance between global integration and local autonomy.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Siemens Aktiengesellschaft -- Case studies; International business enterprises -- Case studies; Customer relations -- Management -- Case studies